The Concentration of Large Extracellular Vesicles Differentiates Early Septic Shock From Infection - Monnamorn, Latthawan; Seree-aphinan, Chutima; Molika, Piyatida; Vichitkunakorn, Polathep; Pattanapanyasat, Kovit; Khwannimit, Bodin; Navakanitworakul, Raphatphorn (Frontiers in Medicine, 2021)
Septic shock represents a subset of sepsis with severe physiological aberrations and a higher mortality rate than sepsis alone. Currently, the laboratory tools which can be used to identify the state of septic shock are limited. In preclinical studies, extracellular vesicles (EVs), especially large EVs (lEVs), have been demonstrated a role as functional inflammatory mediators of sepsis. However, its longitudinal trend during the disease course has not been explored. In this study, the quantities and subtypes of plasma-derived lEVs were longitudinally compared between patients with septic shock (n=21) and non-sepsis infection (n=9), who presented within 48 hours of their symptom onset. Blood specimens were collected for seven consecutive days after hospital admission. lEVs quantification and subtyping were performed using an imaging flow cytometer. The experiments revealed a higher lEVs concentration in septic shock patients than infected patients at the onset of the disease. In septic shock patients, lEVs concentration decreased over time as opposed to infected patients whose lEVs concentration is relatively static throughout the study period. The major contributors of EVs in both septic shock and infected patients were of non-leukocyte origins; platelets, erythrocytes, and endothelial cells released approximately 40%, 25%, and 15% of EVs, respectively. Among lEVs of leukocyte origins, neutrophils produced the highest number of EVs. Nevertheless, the proportion of each subtype of lEVs among the given amount of lEVs produced was similar between septic shock and infected patients. These findings raise the possibility of employing lEVs enumeration as a septic shock identifying tool, although larger studies with a more diverse group of participants are warranted to extrapolate the findings to a general population.